KEARIFAN LOKAL SUKU DUANU DALAM PENGELOLAAN SUMBER DAYA PERIKANAN DI DESA PANGLIMA RAJA KABUPATEN INDRAGIRI HILIR SEBAGAI BAHAN RANCANGAN MODUL BIOLOGI SMA - Rizki, Muhammad; ', Suwondo; ', Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The research has been conducted to determine The Local Wisdom of Duanu Tribe in the management of fishery resources (aquaculture) in the village of Panglima Raja, Indragiri Hilir Regency on April until May 2016. The reserch used to design a module unit of Biology with Biodiversity preservation concept in Senior High School, in two stages namely research or Experiment stage and design a module unit stage. In data collection used in depth interviews with snowball sampling technique to the key informant that is the head of tribe Duanu management in Desa Panglima Raja and Advisory Council of Tribe Duanu for Riau. Besides, the writer also used field observation method and documentation technique. The result of research showed there are some local wisdoms which possessed by tribe Duanu to manage fishery resources, among other are, 1) The planning stage, Tribe Duanu has wisdom in the use of fishing gear as well as the timing of taking the fishes. 2) The use, in this context Duanu communities utilize fishery resources of shrimp, fish, crabs and clams wisely. 3) The control, in this case Duanu tribe use abstinence forbids to preserve the marine keeper of the sea to protect the marine area and fishery resources. 5) The supervision, creating organization of advisor community groups formed by government institutions, in this case is the head of village and 6) The law enforcement by determining punishment for any violators of custom rules. However some customs such as sea semah ceremony and custom’s enforcement process of their ancestors had started in decline or in other words, began to disappear. The results of this research can be used as a material in designing biology module on the concept of biodiversity preservation.Key Words: Local Wisdom, Duanu Tribe, Snowball Sampling, Module Design